1998
DOI: 10.1093/protein/11.5.377
|View full text |Cite
|
Sign up to set email alerts
|

Distinct stability of recombinant L and H subunits of human ferritin: calorimetric and ANS binding studies

Abstract: Thermodynamic and pH stability of recombinant human L- and H-ferritins were probed by differential scanning calorimetry and 8-anilino-1-naphthalenesulfonate (ANS) binding in the pH range 2-7. At pH 2.0-2.8 they were dissociated into subunit monomers and in this pH interval the H-subunit displayed a single calorimetrically-revealed domain with properties of a molten globule-like state: low enthalpy (6.3-8.0 J/g or 169-172 kJ/mol) and Tm of thermal unfolding (approximately 50 degrees C), a wide transition range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 1 publication
2
23
1
Order By: Relevance
“…We found that in the presence of 4.5 M GdnHCl, WT-FTL homopolymers denatured with the higher T m ϳ90°C and MT-FTL at ϳ45°C. Without addition of the destabilizing agent, MT-FTL denatured near 75°C, which is reduced considerably from that reported in the literature (30,32) for the wild type, and again points toward significant destabilization of the mutant. For comparison, FTH1 homopolymers are less stable to heat denaturation than FTL homopolymers, perhaps because of residues located at the intersubunit contacts along the 3-and 4-fold channels and by salt bridges within the 4-helix bundles themselves between Lys-62 and Glu-107 (24,32).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…We found that in the presence of 4.5 M GdnHCl, WT-FTL homopolymers denatured with the higher T m ϳ90°C and MT-FTL at ϳ45°C. Without addition of the destabilizing agent, MT-FTL denatured near 75°C, which is reduced considerably from that reported in the literature (30,32) for the wild type, and again points toward significant destabilization of the mutant. For comparison, FTH1 homopolymers are less stable to heat denaturation than FTL homopolymers, perhaps because of residues located at the intersubunit contacts along the 3-and 4-fold channels and by salt bridges within the 4-helix bundles themselves between Lys-62 and Glu-107 (24,32).…”
Section: Discussioncontrasting
confidence: 60%
“…Both wild type FTH1 and FTL polypeptide subunits are important for the iron storage function of ferritin, with the former containing the ferroxidase site for ferrous iron oxidation and the latter containing the iron nucleation site (2, 3). However, homopolymers composed of FTL subunits have additional properties such as resistance to precipitation under iron loading and being significantly more stable to denaturation by heat and solvent (30,36), and apparently FTL subunits are able to confer these properties upon the heteropolymer. Thus as the first approach to elucidating the effects of the mutation, we compared and contrasted wild type with MT-FTL homopolymers, which have a C terminus of altered length and composition (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 24 subunits come together in a three-dimensional structure that is designed for the dynamic storage of iron; extensive intra-and inter-subunits helix-helix interactions give rise to a very stable protein (it resists up to 80C°, 6M guanidine and pH 3-10) (Martsev et al 1998) yet maintaining sufficient flexibility to allow the flux of iron and other small molecules in and out of its shell (Liu and Theil 2005). The protein actually shows eight narrow hydrophilic channels around the 3-fold symmetry axes and six hydrophobic channels around the 4-fold axes, all with a diameter of about 0.4 nm (figure 1).…”
Section: Mammalian Ferritin Structurementioning
confidence: 99%
“…The contributions of these types of interactions to the folding and stability of the H-and L-subunits differ significantly between the two types of subunits. The intrasubunit hydrogen bonds are about 50% more abundant in the H-subunit than in the L-subunit, whereas the salt bridges are more important in the stabilization of the L-subunit and accounts for about 30% of the stabilization energy of the L-subunit (Martsev et al, 1998). Due to the large number of intra-and inter-subunit salt bridges the ferritin molecule is highly stable to thermal and chemical denaturation (Harrison & Arosio, 1996).…”
Section: Structure Of the Ferritin Protein Shellmentioning
confidence: 99%